Does It Matter Whether One Takes a Test on an iPad or a Desktop Computer?. Issue 4 (1st October 2016) - Ling, Guangming
Abstract : To investigate possible iPad related mode effect, we tested 403 8th graders in Indiana, Maryland, and New Jersey under three mode conditions through random assignment: a desktop computer, an iPad alone, and an iPad with an external keyboard. All students had used an iPad or computer for six months or longer. The 2-hour test included reading, math, and writing items adapted from released NAEP 8th grade tests. Overall, no significant difference was found on the reading, math, or writing section scores or section response time among the three mode conditions. Further, roughly comparable numbers of students reportedly favored testing using an iPad or a desktop computer, but using a preferred mode did not lead to significantly higher section scores. These findings suggest that there is no noticeable disadvantage associated with taking a test on an iPad than on a desktop computer for experienced users of these two studied devices.